Implementasi Kebijakan Pendidikan Inklusif di Sekolah Dasar - Tryas Wardani Nurwan (Journal of Education on Social Science (JESS), 2019)
This study aimed to described implentation of inclusif education in Elementary School 33 Payakumbuh (SDN Negeri 33 Payakumbuh),West Sumatera. This research is based from the problem inclusive education’s policy. This study used descriptive qualitative aproach to research at SD Negeri 33 Payakumbuh as a pilot project for inklusif education in Payakumbuh city. In-depth interviews, document studies, and observations were used to collect data and then analyzed using an Edwards III implementation model which include comunication, resources, and bureaucratic structure. The results of the study indicate that communication are effective. Resources are aspect that requires a lot of improvement, as well as the bureaucratic structure and disposition that is still not a good implementation. The impact of the policy is no discrimination experienced between inclusif student, reguler student, teachers and community.